حجية أفعال النبي صلى الله عليه وسلم ووجوب التآسي بها: دراسة أصولية - الجهني، مسلم بن بخيت محمد الفزي Alfazi, Muslem Bin Bakhit Mohammed (عبد الفتاح محمود ادريس, 2018)
The Sunnah of the Prophet is the second source of legislation, whether it is words, deeds or reports, and the Prophet (peace and blessings of Allaah be upon him) performed many of the rulings that were mentioned in the Holy Book, such as acts of prayer, Hajj and Umrah, etc. Therefore, to explain the ruling of his followers peace be upon him and follow him in it was this research, which is presented to this aspect of the Sunnah purified.
السنة النبوية المطهرة هي المصدر الثاني للتشريع، سواء كانت أقوالا أو أفعالا أو تقريرات، وفعله صلى الله عليه وسلم بين كثيرا من الأحكام التي وردت مجملة في الكتاب الكريم، كأفعال الصلاة، ومناسك الحج والعمرة، ونحوها، ولذا فإن من الأهمية بمكان دراسة هذه الأفعال، لبيان حكم اتباعه صلى الله عليه وسلم والاقتداء به فيها، فكان هذا البحث الذي يعرض لهدا الجانب من جوانب السنة النبوية المطهرة.
Keywords: السنة النبوية -- حجية الأفعال -- محمد صلى الله علية وسلم -- الدلالة الأصولية